THE INFLUENCE OF PROMOTIONAL STRATEGIES ON THE DECISION TO CHOOSE TO STUDY AT BESTARI UNIVERSITY SERANG - Wijaya, Aden; Yubaedah, Ida (Jurnal Bisnis Manajemen dan Akuntansi, 2026)
ABSTRACT This study aims to determine the influence of promotional strategies on the decision to study at Bestari University. The research method used was a quantitative survey. Data collection techniques included initial observations, interviews with the Vice Chancellor, and online questionnaires. Accidental sampling was used as the sampling technique. The results of this study revealed a regression equation: Y =8.207 + 0.568X, with a KD (R2) value of 0.473, or 47.3%. The Pearson correlation coefficient (0.696) ranged from 0.60 to 0.79, indicating a strong influence between promotional variables on the decision to study at Bestari University. The calculated t-value of 6.711 was greater than the t-table value of 0.67964, indicating a significant level (Sig t = 0.001 < 0.05). The remaining 52.7% was influenced by other variables not examined in this study. Keywords: Promotion Strategy, Decision to Choose to Study, Bestari University